Keputusan Memilih Umat Islam dalam Pemilu Legislatif 2024: Citra Kandidat dan Religiusitas - Kodansyah, Riska; Nursalim Malay, M; Natalia, Angga (JURNAL TAPIS, 2025)
Elections are an important indicator of democratic governance in a country. Decisions taken during elections are a form of "expressive" behavior. This study was conducted to determine and analyze the relationship candidate image and religiosity with the decision to vote for Muslims in the 2024 Legislative Election. The research method used in this research is correlational quantitative research method. Data collection techniques and the acquisition of primary data from respondents were obtained by distributing questionnaires through google form media. The sampling technique used in this study was purposive sampling technique. The sample taken in this study amounted to 200 respondents. The results of the data analysis obtained show the coefficient of determination or R-Square (R2) of 0.651, which means that the magnitude of the contribution of the candidate image variable and religiosity to the voting decision is 65.1%. The remaining 34.9% variation in voting decisions is influenced by other variables not included in this study.